Screening of Rice Genotypes for Bacterial Blight of Rice Under Artificial Inoculation Method and Monitoring Field Virulence of Xanthomonas oryzae pv. oryzae - Srinivas, Bhukya; Patil, V. A.; Shinde, C. U.; John, Priya; Garde, Y. A.; Waghunde, R. R. (International Journal of Bio-resource and Stress Management, 2023)
The present study was conducted at the main rice research centre, Navsari Agricultural University, Navsari, Gujarat, India during kharif (July–November, 2020) to study the screening of rice genotypes for bacterial blight of rice under artificial inoculation method and monitoring field virulence of Xanthomonas oryzae pv. oryzae. Thirty genotypes along with two susceptible checks against bacterial blight pathogen under artificial inoculation condition revealed that, 3 genotypes were found moderately resistant viz., NVSR-466, NVSR-396 and ISM. Whereas, 12 genotypes viz., NVSR-411, NVSR-443, NVSR-447, NVSR-453, GNR-6, IR-28, NAUR-1, GNR-2, Gurjari, GNR-4, Krishna kamod and GAR-13 were found susceptible to Xoo and two checks viz., GR-11 and TN-1 were found highly susceptible. Observing to the disease severity, by screening 29 IRBB differentials and two checks employed for research on monitoring virulence of Xoo. Out of 29 differentials, 3 entries were found resistant viz., IRBB-53, IRBB-57 and IRBB-60. Whereas, 3 entries viz., IRBB-50, IRBB-52 and IRBB-61 were moderately susceptible reaction and all the single genes possessing entries were found susceptible to Navsari isolates of Xoo. The goal of this study provided valuable insights to determine the potential management strategies for the disease in rice crops by employing methodology of two rows of 2 meters in length for each entry, the susceptible check TN-1 and GR-11 were planted after the 10th test entry for screening of rice genotypes and monitoring the field virulence of Xoo.